Penerapan Media Audio Book Berbasis Tajwid Untuk Siswa Slow Learner Sekolah Menengah Pertama Muhammadiyah 2 Gresik - Iswanto, Yogi; Amirudin, noor; Yusuf Sya'bani, Mohammad Ahyan (Jurnal Mahasiswa Pendidikan, 2021)
The purpose of this article is to report the results of research by Yogi Iswanto, a student of UMG Aama Islam Study Program, Department of Islamic Religion. The place where the research took place was at SMP Muhammadiyah 2 Gresik. The benefits of this research include: a) introducing UMG students to the university environment, b) increasing the creativity of PAI students in teaching, and c) adding references to learning innovations for educators. The subjects of this study were seventh grade students of SMP Muhammadiyah 2 Gresik. The initial conditions before conducting the research, the researchers made observations about the irregularities of students in the field affected by the pandemic and it turned out that some of the students' characters were still not formed, such as: less active, indifferent, less daring to express opinions, and lack of cooperation or cohesiveness between students. each other and can be called a slow learner. However, after conducting a trial by being given a Tajweed-based audio book media, this was very contradictory. Students began to show enthusiasm in learning and began to pay attention to what was said or done by the subject teacher, as well as the cohesiveness between students and the courage in expressing opinions.